2016
DOI: 10.3389/fnsys.2016.00094
|View full text |Cite
|
Sign up to set email alerts
|

Reward and Behavioral Factors Contributing to the Tonic Activity of Monkey Pedunculopontine Tegmental Nucleus Neurons during Saccade Tasks

Abstract: The pedunculopontine tegmental nucleus (PPTg) in the brainstem plays a role in controlling reinforcement learning and executing conditioned behavior. We previously examined the activity of PPTg neurons in monkeys during a reward-conditioned, visually guided saccade task, and reported that a population of these neurons exhibited tonic responses throughout the task period. These tonic responses might depend on prediction of the upcoming reward, successful execution of the task, or both. Here, we sought to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…These neurons did not give any response to unexpected reward. However, when the target cue was kept on after reward delivery, instead of being turned off, a subpopulation of PPTg neurons showed sustained activity, indicating that the monkey continued fixating on the saccade target even after the reward delivery [163]. This may be indicative of the existence of PPTg neurons that sustain attention toward the actual task event rather than toward reward.…”
Section: The Role Of the Pptg In Predictive Reward Information And Rementioning
confidence: 99%
See 1 more Smart Citation
“…These neurons did not give any response to unexpected reward. However, when the target cue was kept on after reward delivery, instead of being turned off, a subpopulation of PPTg neurons showed sustained activity, indicating that the monkey continued fixating on the saccade target even after the reward delivery [163]. This may be indicative of the existence of PPTg neurons that sustain attention toward the actual task event rather than toward reward.…”
Section: The Role Of the Pptg In Predictive Reward Information And Rementioning
confidence: 99%
“…The tonic reward-related responses consisted of either a sustained increase of discharge [161][162][163], or sustained depression [162]. Most of the sustained increased activity developed from the onset of the initial fixation target until reward delivery, and the magnitude of the response was higher when the shape of the fixation target cued the animal to expect a large reward.…”
Section: The Role Of the Pptg In Predictive Reward Information And Rementioning
confidence: 99%
“…It acts as an integrator of activity from BG, cerebellum, and motor cortex and is an important part of at least three distinct systems: rostral locomotion region, arousal system, and behavioural state control. Indeed, neurophysiological studies in monkeys showed an alteration of firing rate in PPN neurons not only before and during voluntary movements, but also during reflexive and voluntary saccades and fixation (Kobayashi, Inoue, Inoue, Yamamoto, Isa, & Aizawa, 2002; Okada & Kobayashi, 2009, 2014, 2016). The PPN influence upon saccades is probably due to direct PPN projections to SC (PPN cholinergic neurons; Kobayashi, Yoshida, Yoshida, & Inouye, 2009) and STN (predominately inhibitory, GABAergic PPN neuron projections; Mena‐Segovia & Bolam, 2017).…”
Section: Dbs and Eye Movementsmentioning
confidence: 99%